The landslides of 5 May 1998 in Campania, Southern Italy- are they natural disasters or also man-induced phenomena? - Guadagno, Francesco Maria (Journal of Nepal Geological Society, 2000)
Following an intense and prolonged rainfall, debris flows occurred in the Sarno-Quindici region on 4 and 5 May 1998. They took place in an area where recent pyroclastic materials mantle the Mesozoic limestone bedrock. The debris flows extended up to 4 km into the surrounding lowlands and reached four towns causing severe destruction. Generally, they initiate as debris slides or debris avalanches, involving pyroclastic horizons and colluvial soils (0.5-2 m thick) on steep and vegetated slopes at the heads of gullies. These failures, whose slip surface generally coincides with the soil and rock interface, transformed very rapidly to debris flows. Whilst the rainfall was undoubtedly a dominant factor in all of the instabilities, a large number of initial failures occurred where tracks have recently been cut into the pyroclastic veneers. These tracks interrupted the morphological and hydrogeological features of the slopes. The tracks had the cut slope angle significantly higher than that of already steep natural slope. It is thought, therefore, that these conditions have been the main cause of a great number of failures, and, therefore, the origin of the catastrophic flows concentrated within an area of 70 square kilometres.